Pemanfaatan Citra Satelit dan Data Geolistrik untuk Zonasi Daerah Rawan Longsor di Kecamatan Walenrang Barat Kabupaten Luwu - Atfar R, Ranir; Azzahra, Silfa; Annur; Fitriani, Nita; Sari, Sartika; Nurfalaq, Aryadi (JFT: Jurnal Fisika dan Terapannya, 2024)
This research aims to identify areas prone to landslides and landslide slip areas in West Walenrang District, Luwu Regency. The method used to determine landslide-prone areas is the scoring and overlay method, while to identify landslide slip areas using the dipole dipole configuration geoelectric method with a measurement path length of 100 m. The data used in scoring and overlaying are land cover data obtained from Landsat 8 satellite imagery, rainfall data and slope slope data originating from DEMNas. The results of this research show that most of the West Walenrang District is an area with a very high level of landslide vulnerability. The distribution of landslide-prone areas in West Walenrang District is in the low category, namely in Lewandi Village and Ilan Batu Village. Areas of moderate vulnerability are spread across a small part in Lewandi Village, Lamasi Hulu Village, Pasang Village, Lempe Village, Ilan Batu Uru Village, and Ilan Batu Village. Areas with high vulnerability are Lempe Village and Pasang Village. Meanwhile, areas with a very high level of vulnerability are spread across most of West Walenrang District, including Lewandi Village, Lamasi Hulu Village, Pasang Village, Lempe Village, Ilan Batu Uru Village, and Ilan Batu Village. The landslide slip area is interpreted as basalt rock which has a resistivity of 2,925 Ohm - 18,585 Ohm.m with a slope of 25.47o at a depth of 5.13 m - 17 m. The resulting landslide potential is in the form of a rotational type landslide.